Chordoid glioma of the third ventricle—a case report and literature review - Chou, Ying-Hsiang; Tseng, Hsien-Chun; Lee, Yueh-Chun (Therapeutic Radiology and Oncology, 2018)
Chordoid glioma (CG) is a very rare brain tumor. According to the World Health Organization (WHO) classification, it is classified to be a low-grade glioma, class II. It often arose from the third ventricle, along the roof of the ventricle, or the anterior wall of the ventricle. Due to the location of the tumor, the tumor frequently involves the thalamus or hypothalamus region. A 44-year-old man was presented with severe headache, dizziness and unsteady gait for 2 weeks. MRI showed a lesion sized 53 mm × 46 mm in the third ventricle involving right thalamus. Stereotactic brain biopsy was done and diagnosed to be CG. External beam radiotherapy (EBRT) using TomoTherapy® was delivered with a dose of 62 Gy in 31 fractions. The tumor responded to the treatment but progressed 5 months after the radiotherapy. The patient died from urosepsis with multi-organ failure 10 months after the radiotherapy. The most common clinical presentation for CG was headache. Neuroradiologically, the tumor was distinct in its location and pattern of intensity in MRI. Histopathologically, the tumor was characteristics with cords or clusters of epithelioid cells resembling chordoma with lymphocyte infiltration. The disease is usually treated by gross total resection (GTR), with promising outcome. For those who are unsuitable for total resection, subtotal resection (STR) or biopsy followed by radiotherapy was performed in some literatures. The role of radiotherapy was not clear in this disease. Literatures regarding this disease and the role of radiotherapy were reviewed and discussed.